Evaluation of germination and hydopriming effect on increasing germination potential in native stands of parsley (Petroselinum crispum) - seyed abbas Mirjalili; elahe poorazizi (علوم و فناوری بذر ایران)
Parsley, which today is classified as a vegetable, has many properties and is used in food and pharmaceutical industries. The seeds of the native populations of this plant do not have a good germination percentage and many efforts are being made to improve the growth and germination of the seeds. In order to investigate the seed germination rate of native stands and the effect of hydropriming treatment in increasing the germination power of the seeds of these stands, an experiment was conducted in the form of a completely randomized design at four time levels (12, 24, 48 and 72 hours) against the control and with four replications among 24 native stands collected from different parts of the country and two populations with foreign origin imported were carried out. The results showed that the average seed germination percentage of the stands before treatment was 56.7% (the lowest rate was 20% in curled leaf Parsley stand and the highest was 78% in Jiroft 1 stand). Also, the hydropriming treatment had a significant effect at the level of 1% on the emergence of parsley seeds, and its greatest effect was in 24 hours. Also, the highest effect of treatment on Arak, Garmsar and Pich of Tehran was 21.8, 20.9 and 20%, respectively. The least effect of hydropriming was on the population of curled leaf parsley (7.4%). Totally, it was concluded that hydropriming can increase the germination percentage and quality of parsley seeds.